UJI PELINDIAN SENYAWA-SENYAWA TEMBAGA DAN TIMAH HITAM SETELAH STABILISASI/SOLIDIFIKASI DENGAN SEMEN PORTLAND MENGGUNAKAN ROTARY AGITATOR - Ardeniswan Ardeniswan (Jurnal Kimia Terapan Indonesia, 2010)
In this study, wastewater used in the experimental is an artificial wastewater containing copper and lead with each concentration of 500 mg/L. Metal ions were precipitated as hydroxide compounds [Cu (OH2, Pb(OH)2] and sulfide compounds (CuS, PbS). The precipitate partly was direct leached tested and the other part was stabilized/solidified by using Portland cement. Furthermore, TCLP test (Toxicity Characteristic Leaching procedure) was done by using the Rotary Agi tator with rotational speed 30±2 rpm for 18±2hours.From the TCLP test results showed that the compounds of CU(OH)2 and Pb(OH)2 leached without solidification process which carried out with Portland cement, both are 0.86 mg/L and 45.6 mg/L. While thecompounds CuS, and PbS leached also without solidification process which carried out with Portland cement, are424mg L; and 159 mg L.When the compounds of Cu(OH)2, CuS, Pb(OH)2, PbS were stabilized/solidified with Portland cement at the ratio 1:1, apparently both of copper ions from Cu(OH)2, and lead ions from Pb(OH)2 did notexperience leaching. In contrast to copper ions in the form of CuS, and lead ions in theform PbS, leaching was experienced at 3.56 mg/L and 1.16 mg/L. These values were still below the required quality standard for TCLP.Keyword : wastewater, heavy metals, hazardous waste, stabilization/solidification, TCLP test.